2016
DOI: 10.17245/jdapm.2016.16.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative nausea and vomiting after general anesthesia for oral and maxillofacial surgery

Abstract: BackgroundPostoperative nausea and vomiting (PONV) is one of the most common postoperative complications. Despite this, few papers have reported the incidence and independent risk factors associated with PONV in the context of oral and maxillofacial surgery (OMFS). Therefore, we sought to determine the incidence of PONV, as well as to identify risk factors for the condition in patients who had undergone OMFS under general anesthesia.MethodsA total of 372 patients' charts were reviewed, and the following potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 31 publications
2
29
0
3
Order By: Relevance
“…However, whether obesity is a risk factor for PONV is controversial. A relatively high body mass index (BMI) may promote PONV [8,11], but the opposite effect has also been reported [12][13][14]. Others have found that BMI is not a risk factor for PONV [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, whether obesity is a risk factor for PONV is controversial. A relatively high body mass index (BMI) may promote PONV [8,11], but the opposite effect has also been reported [12][13][14]. Others have found that BMI is not a risk factor for PONV [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative nausea and vomiting (PONV), as one of the most common and most annoying complications after laparoscopic cholecystectomy, occurs in more than 40% - 77% of the cases ( 1 ). PONV causes aspiration, hypoxia, bleeding, suture rupture, patient discomfort, increased hospital stay, and increased hospital costs ( 2 ). Preoperative drugs that are used intravenously to prevent PONV include endostenone, troposterone, granistorone, dilustran, metoclopramide, and perphenazine.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the incidence of PONV was similar in NTI and LMA groups. Postoperative nausea and vomiting might be more affected by the anaesthetic drug used [26][27][28] , or the type of surgery performed rather than by the airway management technique. It should be noted that all children in both groups received an antiemetic intravenously during the operation, which might explain the decreased incidence of nausea and vomiting in both groups.…”
Section: Discussionmentioning
confidence: 99%